Compensation for Bank Depositors in Iraq - Al-Jaf, Mohammed Omer Ali (Technium Social Sciences Journal, 2021)
This paper attempts to explain Compensation of bank depositor In Iraq. It relies on the regulation no 33 of 2016 in its definition of a company which must be established in accordance with that regulation. Accordingly, there is an Iraqi judicial company named Iraqi Deposit Insurance Company (IDIC). With its autonomous entity as well as own capital, the company manages to achieve the purposes of its establishment. It has a net worth of 100,000,000,000 Iraqi Dinars which facilitates its ability to invest from its financing sources. The main motive for the establishment of this company was to instill confidence in people and to stabilize the country as the academics have advised. In conclusion, taking advantages from many other countries, we recommend that an act be enacted by the Iraqi legislature to strengthen bank deposit guarantee.